Predisposing factors of preeclampsia and eclampsia in persons referring to governmental hospitals of Hormozgan province (1994-95) - Golkhajeh, F (Iran University of Medical Sciences, 1999)
This survey assessed predisposing factors of preeclampsia and eclampsia in persons referring to governmental hospitals of Hormozgan province. Samples of this study were pregnant women who had preeclampsia and eclampsia and also pregnant women who had not preeclampsia and eclampsia (control group) referring to governmental hospitals of Hormozgan province from September 1994 to February 1995. All of these women resided in this province from onset of their pregnancy and from different area of this province refer to three governmental hospitals. Total number of samples was 120 pregnant women who had preeclampsia and eclampsia and 200 women who were in control group. Data gathering was performed by questionnaire and interview with the samples. Questionnaire included demographic data and personal, familial, and socio-economical predisposing factors. Statistical tests revealed that significant relationship was exist between incidence of preeclampsia-eclampsia and primigravida, use of contraceptive methods that inhibit contact of sperm and semen with endometrium, history of preeclampsia- eclampsia in previous pregnancies and in the family, weight, site of habitancy and duration of habitancy in province. No significant relationship was exist between incidence of preeclampsia-eclampsia and age, nutritional status, history of renal diseases, diabetes, and chronic hypertension, Multiple pregnancy, and financial status of family. Some findings of this study were similar to findings of other studies. According to results of this study, some implications for practice and also for other midwifery and health researches were suggested.